Tlymphocyte cells and t helper cells response following bee propolis supplementation and endurance running - Muin, Maziana Binti Abdul (Universiti Sains Malaysia, 2016)
To date, to our knowledge, no study has been carried out to investigate the effect of bee propolis supplementation on T lymphocyte cells and Thelper (Th) cells count following endurance running among male recreational runners. To investigate the effect of bee propolis supplementation on T lymphocyte cells and Th cells count following endurance running among male recreational runners. In this study, eleven participants (age: 21.0 ± 1.5 years; BMI: 22.3 ± 2.5 kg/m2) were recruited whereby they carried out 3 preliminary tests which involved a submaximal test, a maximum oxygen uptake (VO2max) test and a familiarisation test. After that, participants performed the first running trial which involved 90 min running at 60% VO2max after an overnight fast. After that, participants consumed bee propolis tablets (500 mg/tablet) for 4 weeks, 2 tablets per day. After 4 weeks of the supplementation period, participants performed the second running trial (90 min running at 60% of VO2max)- For each running trial, blood samples were collected from the participants before, during, post-, and 1 h post-exercise for analysing T and Th cells count. Oxygen uptake (VO2) and rate of perceived exertion (RPE) were recorded before, during and after exercise. Endurance exercise significantly increased T lymphocyte cells count and Th cells count during the first 30 min of exercise but then decreased until the end of exercise and continue to decrease 1 hour post-exercise. In addition, the present study also discovers that T lymphocyte cells count and Th cells count were not significantly different between the pre- and post supplementation trials. Similarly, VO? and RPE were not significantly different between both trials The present findings showed that there were no significant effect of bee propolis supplementation on the T lymphocyte and Th cells count, VO2 and RPE following endurance running in male recreational runners.